Global Development Finance 2007, 1 : (Analysis and Outlook) The Globalization of Corporate Finance in Developing Countries. - Bank, World (Online access: World Bank World Bank Open Knowledge Repository., 2007)
Global Development Finance (GDF), is the World Bank's annual review of recent trends in and prospects for financial flows to developing countries. It is an indispensable resource for governments, economists, investors, financial consultants, academics, bankers, and the entire development community. Vol I: Analysis and Outlook reviews recent trends in financial flows to developing countries. Also available as a two volume set, Vol II. Summary and Country Tables* includes comprehensive data for 138 countries, as well as summary data for regions and income groups.